PURPOSE SOFTWARE SYSTEM FOR COMMUNICATION NETWORK OPERATING DATA - Syahril Syahril Syahril (Majalah SIKOMTEK, 2004)
Data communication can be developed through the propagation of radio waves. Datacommunication via radio is able to overcome the problem of limited telecommunicationfacilities in remote areas who have limited means of communication. In general, datacommunication can be said as the process of sending data or information which have beenmodified in a certain code (convert it into electrical signals) and data is transmitted.Transmission medium can be via satellite (VSAT-Very Small apertures Terminal), telephonecable, or via radio waves (HF / VHF / UHF).